2020
DOI: 10.1097/md.0000000000023341
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral problems of Mandarin-speaking late-talking toddlers and preschool aged children

Abstract: This study aimed to examine whether Mandarin-speaking late-talking (LT) toddlers have a higher incidence of behavioral problems than typical language developing (TLD) children in toddlerhood and at preschool age from a community sample in Taiwan. This prospective case–control study comprised 32 LT and 32 TLD toddlers. Participants’ parents provided reports about their children at 2 and 4 years using the Child Behaviors Checklist, a component of the Achenbach System of Empirically Based Assessment. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…It is important to note that we utilized a definition of LT status that included two possible criteria: a child was classified as an LT if either they had a vocabulary score on the MCDI at or below the 15th percentile or they were not combining words. Using low expressive vocabulary or lack of word combinations to define LTs is consistent with definitions used in previous studies and in clinical settings (Beckage et al, 2011;Hodges et al, 2017;Lu et al, 2020;Rescorla et al, 1997;Rescorla & Schwartz, 1990). However, the youngest children in the current study were 22 months of age, which is 2 months younger than the typical criterion of not combining words by 24 months.…”
Section: Expressive Vocabulary Assessment and Classification Into Tt ...supporting
confidence: 83%
See 2 more Smart Citations
“…It is important to note that we utilized a definition of LT status that included two possible criteria: a child was classified as an LT if either they had a vocabulary score on the MCDI at or below the 15th percentile or they were not combining words. Using low expressive vocabulary or lack of word combinations to define LTs is consistent with definitions used in previous studies and in clinical settings (Beckage et al, 2011;Hodges et al, 2017;Lu et al, 2020;Rescorla et al, 1997;Rescorla & Schwartz, 1990). However, the youngest children in the current study were 22 months of age, which is 2 months younger than the typical criterion of not combining words by 24 months.…”
Section: Expressive Vocabulary Assessment and Classification Into Tt ...supporting
confidence: 83%
“…The MCDI is a standardized and norm‐referenced caregiver report measure of children's communication development, including expressive vocabulary and syntax. Toddlers who received a score at or below the 15 th percentile (Beckage et al., 2011; Hodges et al., 2017; Lu et al., 2020), and/or children who had no reported two‐word combinations were classified as LTs. All other children were classified as TTs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of early-life language development and later cognitive functions, our findings are consistent with the one study in a British cohort reporting that delays in speaking in infancy were associated with lower IQ at age 8 and poorer cognitive functions at ages 26 and 53 years [ 9 ]. Three other cohort studies have reported the effect of delays in language/communication attainment on the risk of emotional and behavioral problems [ 11 , 47 , 48 ]. It is well-documented that some children are affected by co-occurring language delay and neurobehavioral problems [ 49 , 50 , 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Internalizing and externalizing behaviors may follow different developmental pathways [18]. Previous studies found that a 2-year-old children with low receptive language abilities were at risk of internalizing behaviors [19,20]. However, whether LT toddlers with behavior problems in later developmental stages (e.g., preschool age) show temporal stability from early behavior problems was unclear.…”
Section: Introductionmentioning
confidence: 99%